The secret history of the rape kit : a true crime story - Kennedy, Pagan, 1962- (Vintage Books, a division of Penguin Random House LLC, 2025)
"A thrilling, novelistic work of journalism that uncovers the remarkable and hidden story of Marty Goddard, the woman who invented the rape kit, changed the course of how we treat sexual assault forever, and then vanished from the record. The idea came to Marty Goddard in 1971. She was working at a crisis hotline, haunted by the stories of survivors and plagued by two principle questions: Why were so many predators getting away with crimes? And, how do we stop them? In the coming years, Marty set off a massive campaign that lobbied to have sexual assault treated and investigated as the crime that it is. By creating the first rape kit, she revolutionized forensics. The kit would live on as one of the most powerful and effective tools for bringing perpetrators to justice. Marty, however, and any record of her, simply disappeared. The Secret History of the Rape Kit chronicles the story of one journalist's mission to uncover the story and woman behind an invention that transformed the lives of women the country over. As Pagan Kennedy peels back the layers behind the history of the kit and Marty's life, she falls into a deeper and deeper obsession. As she pursues this overlooked but critical story from our past, she dives into the inequities built into our patent system and our understanding of technological progress, the problematic and gendered history of forensics, and sexual forensics in particular, the misogyny that runs rampant in police departments, the legacy of Marty's invention and the failings that persist in how we prosecute rape. And, as Pagan unearths who Marty really was, and what happened to her, she reflects on her own experiences with sexual assault, and how one forgotten woman's legacy could have saved her, as it has so many"--